Benefit Value of Mangrove Forest in Sarawet Village, Likupang Timur, Minahasa Utara - Tamsir, Chika Litawaty; Lasabuda, Ridwan; Wantasen, Adnan S.; Kondoy, Khristin I. F.; Kambey, Alex D.; Sondak, Calvyn (Sam Ratulangi University, 2022)
The purpose of this study is to: 1) identify various types of direct and indirect benefits of mangrove forests, and 2) estimate the total economic value of the mangrove forest in Sarawet Village. This type of research is descriptive and quantitative using survey methods. Data analysis in this study uses descriptive and quantitative analysis. Descriptive analysis is used to explain the activities of utilizing natural resources of mangrove ecosystems, while quantitative analysis is used to calculate the total economic value of mangrove ecosystems. The selection of respondents used the purposive sampling method, with a total of 76 respondents. Analysis of the total economic value for the value of direct benefits using market prices, and the value of indirect benefits using replacement costs. The results showed that the people of Sarawet Village use the mangrove forest ecosystem directly in the form of mangrove wood used as firewood and fence stakes, leaves Nipah are made with roofs, and the community carries out fishing and crab activities around mangrove waters.Analysis of the total economic value of the mangrove forest in Sarawet Village amounted to Rp. 6.884.344.178,-/year. The total economic value is obtained from the value of direct benefits including utilization as firewood Rp. 4,160,000,- /year; fence pegs Rp. 87.500,-/year; roof of the house Rp. 330.000,-/year; fishing Rp. 769.174.000,-/year; crab fishing is Rp. 190.320.000,-/year, and the value of indirect benefits is as a barrier to abrasion and seawater waves Rp. 5.920.272.678,-/year. The large economic value of the total mangrove forest ecosystem in Sarawet Village shows that the mangrove ecosystem provides great benefits to the community.Keywords: direct benefit value, indirect benefit value, total economic value, MangroveAbstrakThe purpose of this study is to: 1) identify various types of direct and indirect benefits of mangrove forests, and 2) estimate the total economic value of the mangrove forest in Sarawet Village. This type of research is descriptive and quantitative using survey methods. Data analysis in this study uses descriptive and quantitative analysis. Descriptive analysis is used to explain the activities of utilizing natural resources of mangrove ecosystems, while quantitative analysis is used to calculate the total economic value of mangrove ecosystems. The selection of respondents used the purposive sampling method, with a total of 76 respondents. Analysis of the total economic value for the value of direct benefits using market prices, and the value of indirect benefits using replacement costs. The results showed that the people of Sarawet Village use the mangrove forest ecosystem directly in the form of mangrove wood used as firewood and fence stakes, leaves Nipah are made with roofs, and the community carries out fishing and crab activities around mangrove waters.Analysis of the total economic value of the mangrove forest in Sarawet Village amounted to Rp. 6.884.344.178,-/year. The total economic value is obtained from the value of direct benefits including utilization as firewood Rp. 4,160,000,- /year; fence pegs Rp. 87.500,-/year; roof of the house Rp. 330.000,-/year; fishing Rp. 769.174.000,-/year; crab fishing is Rp. 190.320.000,-/year, and the value of indirect benefits is as a barrier to abrasion and seawater waves Rp. 5.920.272.678,-/year. The large economic value of the total mangrove forest ecosystem in Sarawet Village shows that the mangrove ecosystem provides great benefits to the community.Keywords: direct benefit value, indirect benefit value, total economic value, Mangrove.